Imagined states: nationalism, utopia, and longing in oral cultures - Del Giudice, Luisa, editor; Porter Gerald, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2001)
An international ensemble of folklore scholars looks at varied ways in which national and ethnic groups have traditionally and creatively used imagined states of existence--some idealizations, some demonizations--in the construction of identities for themselves and for others.
Mountains of cheese and rivers of wine: Paesi di Cuccagna and other gastronomic utopias / Luisa Del Giudice -- Prefaced space: tales of the colonial British collectors of Indian folklore / Sadhana Naithani -- Working the railways, constructing Navvy identity / Reimund Kvideland and Gerald Porter -- "Who talks of my nation?" the role of Wales, Scotland, and Ireland in constructing "Englishness" / Gerald Porter -- The Turkish German self: displacing German-German conflict in oriental street ballads / Tom Cheesman -- Bovine bodies and the domestication of the human mind / Cozette Griffin-Kremer -- "The poppy blossom from my native land": the married woman as exile in Latvian folk poetry / Vaira Vike-Freiberga.
Keywords: Oral tradition; Utopias; Imaginary places; Ethnicity; Nationalism; Nostalgia